Pengaruh Inklusi Keuangan, Pengelolaan Keuangan dan Penggunaan E-Payment terhadap Kinerja Keuangan UMKM Sektor Industri Pertanian di Kabupaten Buleleng - Handayani, Kadek Ayu; Suwena, Kadek Rai (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This study aims to determine the influence of the variables of the Effect of Financial Inclusion, Financial Management and the Use of E-Payment on the Financial Performance of MSMEs in the Agricultural Industry Sector in Buleleng Regency. The population in this study were agricultural MSMEs in Buleleng Regency. The number of samples used in this study were 163 respondents using the Slovin formula. The sampling technique in this study was proportional random sampling technique. The data in the study were collected by distributing questionnaires. Data processing in this study used the help of the Statistical Package for the Social Science (SPSS) program version 25. The analysis technique used is multiple linear regression analysis with partial (t test) and simultaneous (f test) hypothesis testing. The results of this study indicate that: (1) The effect of Financial Inclusion on financial performance, (2) The effect of Financial Management on financial performance, (3) The effect of E-Payment Use on financial performance, (4) The effect of Financial Inclusion, Financial Management, and E-Payment Use on the Financial Performance of Agricultural Industry Sector MSMEs in Buleleng Regency.